THE ROLE OF TECHNOLOGY IN EDUCATION - Shermamatova , Zaynab Azimjonovna; Isomiddinova , Aziza Isomiddinovna; Naimova , Laylo Nabiyevna (Educational Research in Universal Sciences, 2023)
The era of 21st century is often regarded as the era of technology. Today, technology plays an important role in our life.Therefore, we can not realize our lives without technology. Since, it supports to make our life easy. The impact of technology can be felt in every possible field and one such field is education. In the present day, the significance of educational technology in teaching has increased due to the utilization of information and communication technologies (ICT). Educational technology involves the systematic application of modern technology to enhance the standard of education. It offers a structured approach to conceptualizing and assessing the educational process, encompassing learning and teaching, and assists in implementing contemporary teaching methods. This paper aims to conceptually investigate the evolving roles of technology in education.